Ex vivo assessment of the buccal and oral bone by CBCT - Rütters, Maurice; Kim, Ti-Sun; Hagenfeld, Daniel; Kronsteiner, Dorothea; Gehrig, Holger; Lux, Christopher J.; Şen, Sinan (Journal of orofacial orthopedics, 2021)
Identifying buccal and oral bone as an important supporting periodontal structure for teeth provides important information for treatment planning in periodontics and orthodontics. This study aims to add evidence to the knowledge of preciseness of cone beam computed tomography (CBCT) measurements of the vertical dimension of buccal and oral bone. The hypothesis is that CBCT is an accurate and reliable method to measure vertical vestibular and oral bone loss.